Pemanfaatan Chitosan Dari Limbah Kulit Udang Sebagai Pestabil Pada Nanopartikel Perak Dengan Bioreduktor Daun Serai (Cymbopogon citratus) - Fatimah; Islawati; Asdinar; AR.Pratiwi Hasanuddin (Jurnal Kesehatan Panrita Husada, 2021)
This study was based on the background Renewable research in nanotechnology has shown the creation of new, better performing products. Nanoparticles are part of nanotechnology which plays an important role in the development of science, especially its application in various fields including the health sector Chitosan has been widely applied commercially in the chemical, food and pharmaceutical industries. Chitosan can be a stabilizer alternative in the formation of silver nanoparticles.The purpose of this study was to determine the use of chitosan from shrimp shell waste as a stablizer on silver nanoparticles with lemongrass leaf as bioreductor. This research is a type of experimental research. Experiments were carried out to determine the ability of chitosan from shrimp shell waste as a stabilizer in silver nanoparticles with lemongrass leaf as bioreductor. Based on the results of the research, the spectrum shows that the silver nanoparticles without the addition of chitosan are formed at a maximum wavelength of 442 nm - 448 nm, while for silver nanoparticles with the addition of chitosan are at a wavelength of 458 nm - 470 nm. The conclusion Chitosan from shrimp shell waste can be used as a stabilizer in silver nanoparticles with lemongrass leaf as bioreductor with a maximum wavelength of 470 nm with a synthesis time of up to 72 hours with an absorbance value of 0.610 nm.